2018
DOI: 10.1155/2018/1267038
|View full text |Cite
|
Sign up to set email alerts
|

Mice Selected for Acute Inflammation Present Altered Immune Response during Pristane-Induced Arthritis Progression

Abstract: Mouse lines selected for maximal (AIRmax) or minimal acute inflammatory reaction (AIRmin) were used to characterize the immune response and the influence of genetic background during pristane-induced arthritis (PIA). Susceptible AIRmax mice demonstrated exacerbated cellular profiles during PIA, with intense infiltration of lymphocytes, as well as monocytes/macrophages and neutrophils, producing higher levels of IL-1β, IFN-γ, TNF-α, IL-10, total IgG3, and chemokines. Resistant AIRmin mice controlled cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In this context, IL-12 is also an important cytokine for its ability to stimulate the functions of NK cells, macrophages, and T lymphocytes [ 22 ]. High CD8 + cell, IL-12, and IL-10 levels, and lower IFN- γ production in the AIRmax mice were previously observed in different situations [ 22 , 36 , 38 , 40 ] and demonstrated a delicate balance between the nature of the stimulus and the host response.…”
Section: Discussionmentioning
confidence: 77%
“…In this context, IL-12 is also an important cytokine for its ability to stimulate the functions of NK cells, macrophages, and T lymphocytes [ 22 ]. High CD8 + cell, IL-12, and IL-10 levels, and lower IFN- γ production in the AIRmax mice were previously observed in different situations [ 22 , 36 , 38 , 40 ] and demonstrated a delicate balance between the nature of the stimulus and the host response.…”
Section: Discussionmentioning
confidence: 77%
“…Besides their central role in inflammasomes for cytokine release, ASC specks can be released to the extracellular space, accumulate in inflamed tissues and can be internalized by surrounding inflammatory cells inducing inflammation chronicity or amplification, therefore worsening the disease or contributing to cure (26,27). The AIRmax and AIRmin mouse lines differ in natural resistance to infections, to the induction of autoimmune diseases and chemical carcinogenesis as well as in tissue repair capacity (18,19,(28)(29)(30)(31)(32)(33)(34). These phenotypes might be influenced by the differential Irm1 locus-dependent inflammasome activation between the two lines described here.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of their divergent inflammatory response, we have demonstrated that AIRmax and AIRmin mice differ in their susceptibility to bacterial infections (17), tumorigenesis (18,19), and autoimmune diseases (20,21). With regard to systemic and local responses induced by BjV, both lines are equally susceptible to venom-induced lethality, showing similar LD 50 .…”
Section: Introductionmentioning
confidence: 94%